In vivo biodistribution analysis of transmission competent and defective RNA virus-based episomal vector - Komatsu, Yumiko; Tanaka, Chiaki; Komorizono, Ryo; Tomonaga, Keizo (Scientific reports, 2020)
RNA virus-based episomal vector (REVec) is an emerging viral vector system that mediates long-term stable gene expression in variety of cell types in vitro . However, little is known about its tissue tropism and persistence of gene expression in vivo . Here, to evaluate the feasibility of REVec for in vivo gene delivery, we conducted biodistribution analysis of transmission competent REVec and transmission defective ΔG-REVec in Lewis rats. Following intracranial administration of REVec, transgene expression was detected in various tissues. In contrast, transgene expression was only observed in the brain after ΔG-REVec administration. Low levels of vector shedding in the feces and blood and of neutralizing antibody in the serum were detected after REVec injection. In the brain, microglia, astrocytes and neurons were susceptible to REVec-mediated transduction. However, the animals administered with REVec, but not with ΔG-REVec showed a significant decrease in body weight compared to mock treated animals. Additionally, CD8 T cell infiltration was observed in the brain of these animals. In summary, we demonstrated that REVec promotes long-term transgene expression in vivo without causing high vector shedding or neutralizing antibody production; however, suggests the need to attenuate vector associated pathogenicity in the future.